The right of aliens to hold interest in land: demystifying the conundrum of "all Nigerians" and "any person" as used in the land use act (2017)
The role of the courts through its interpretative jurisdiction to the development and overall growth of a nation cannot be over emphasised. The laws become policy statements when given life by the courts. In doing so, the courts must strike a balance between interpreting the letters of the law and adopting an interpretative approach that will enhance the socio- economic development of all persons resident within the territorial jurisdiction of the State. Laws made and Interpreted must reflect an intention to protect these sets of individuals and enhance their well-being. Consequently, this paper examines the provisions of LUA as it relates to the rights of aliens to own interest in land in Nigeria. The aim is to determine whether the lawmakers intend to restrict an alien from holding interest in land. This examination is crucial if it is considered that land plays an important role in economic development of any society. Therefore. this paper argued that the right to work of many occupations is invariably- tied to land and. as a result, the court in interpreting the provisions of the L UA must give it its widest interpretation